Enhancement of Thermal–Acoustic Properties of Pinus Radiata by Impregnation of Bio-Phase-Change Materials - Vasco-Calle, D; Urzua-Parra, I (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Using fatty acids has generated significant interest in the building sector for improving energy storage in the form of latent heat. In this work, using vacuum impregnation, we analyzed the properties of a capric acid and myristic acid eutectic (83-17%) as a bio-based phase change material in Pinus radiata. The delignification of Pinus radiata samples facilitated the impregnation process, which was carried out using the Kraft pulping method. Morphological, chemical, mechanical, thermal, and acoustic impedance analyses were performed. The results revealed that impregnating PCM in Pinus radiata samples increases the thermal inertia of the impregnated samples, which is comparable to that of delignified samples. Additionally, the analyses showed no significant difference between natural and delignified samples after treatment with PCM. © 2025 by the authors.